Effect of spatial variability of earthquake ground motions on the reliability of road system. Issue 136 (September 2020) - Ering, Pinom; Sivakumar Babu, G.L.
Abstract: This paper presents an approach for assessing the failure probability of a road system due to its interaction with landslides induced by the earthquake. The landslide occurrence and failure probability of the road system is estimated by considering the spatial variation of earthquake ground motion. Since significant incoherence in earthquake ground motions is usually observed within the spatial dimensions of large horizontally expanded structures like roads, bridges and dams, it is important to consider the uncertainty due to spatially varying ground motion. The stochastic nature of seismic loading is incorporated in the study by generating a series of earthquake ground motions while the spatial variation of ground motion is accounted for by using cross power spectral density function. Two phase material point method (MPM) is used to simulate the dynamic behaviour of saturated slopes. MPM is able to capture the failure mechanism of slopes under seismic loading and evaluates the travel distance of sliding mass. Highlights: Since significant incoherence in earthquake ground motions are usually observed within the spatial dimensions of large horizontally expanded structures like roads, it is important to consider the uncertainty due to spatially varying ground motion. Two phase material point method (MPM) is used to simulate the dynamic behaviour of saturated slopes and evaluates the travel distance of sliding mass. The effects of spatial variation of ground motion on the performance of slopes and the reliability of road system has been investigated. The results show that ignoring the spatially variability of ground motion may lead to underestimation of landslide risk as well as risk of road system.